Model za določanje življenjske dobe lesa listavcev - Žlahtič Zupanc, Mojca (Les (Ljubljana), 2017)
The majority of Slovenian wood species do not have durable wood. Due to increased environmental awareness, users are avoiding treated wood and wood from tropical forests. In order to increase the consumption of domestic wood species, we have to understand the overall performance of wood better. Therefore, a study of the most important Slovenian hardwood species was performed, as prescribed by Meyer-Veltrup et al. Durability against wood decay fungi and wetting was determined using standard laboratory tests. These data were then used for calculation of the respective factors needed for calculation of predicted service life.
Keywords: durability; glive razkrojevalke; les; moisture content; odpornost lesa; ood decay fungi; service life; vlažnost lesa; wood; wood protection; zaščita lesa; življenjska doba